Wyznaczanie Częstości Skrętnych Drgań Własnych Silnika Rzędowego z Dołączonymi Masami Bocznymi - Ripianu, A. (Engineering Transactions, 1961)
This paper presents a method for determining the frequency of torsional vibration of a row engine crankshaft with counterbalance weights. The method proposed by O. KRAMER and B. FRANK and completed by R. ARNOLD is applied here to a relatively complex case. It enables us to find the natural frequency, no tests being carried out. The case of a k-cylinder row engine with six counterbalance weights is considered. It is stressed that analagous considerations may be done for any number of coun-terbalance weights. The method described is based on the notion of the reduced mass, dynamically equivalent to a system of masses. A numerical example is given by determining the natural vibration of the cranks-haft of a six-cylinder engine with six counterbalance weights.